Obstacle Avoidance Functions on Robot Mirosot in the Departement of Informatics of UPN “Veteran” - Wilis Kaswidjanti; Hidayatulah Himawan; Awang Hendrianto Pratomo; Hafidz Fajar Abdur Rahman (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
The robot is a machine that can perform physicalactivity repeatedly, either with human control or worksautomatically with the use of artificial intelligence. In the process,the robot can perform various kinds of sports, one of which is abranch of football. Robot football match organized by theFederation of International Robot-Soccer Association (FIRA)consists of several categories, one of which Micro Robot SoccerTournament (MiroSot). MiroSot is five to five games consisting of arobot measuring 7.5 cm x 7.5 cm x 7.5 cm were able to move andadapt to the environment without human intervention. CurrentlyInformatics UPN "Veteran" Yogyakarta began to develop MiroSotbut there are still some problems found that the movement of therobot is irregular, so that frequent collisions of the robot opponent.So it takes a function to avoid obstacles on the robot MiroSot.Capitalize knowledge of Obstacle Avoidance of the book "SoccerRobotics" [1], the function of avoiding obstacles using the potentialfield based navigation univector algorithm to determine the futurepath of the robot and dodge the functionality tailored to thecharacteristics of the robot MiroSot Information Engineering UPN"Veteran" Yogyakarta. The program is created usingprogramming language C ++ with Visual Studio 2008 IDE and sentto the robot from the main computer via radio frequency, the robotcan move properly using speed camera support above 50 framesper second as robot vision. Function to avoid obstacles on the robotdefender position MiroSot in the Departement Informatics of UPN"Veteran" Yogyakarta made this using the function position tomove towards the goal and using mathematical calculations todetermine the movement path avoiding obstacles based on potentialfield. In the development of this function can avoid obstacles in theform of a robot team, not only the robot opponent avoided. Whenthe moving speed of the robot was given control of the speeddepends on the distance of the destination position or positions arealso obstacles. The use of sensors gyroscrope expected to provide aneffective movement while avoiding obstacles. The success rate usinga gyroscope sensor to avoid obstacles on the position of defender of96% and the average time needed to reach the goal position at 5:33seconds so much faster.